Pharmacokinetics of meropenem during advanced organ support (ADVOS®) and continuous renal replacement therapy. Issue 10 (October 2021) - König, Christina; Kluge, Stefan; Fuhrmann, Valentin; Jarczak, Dominik
The advanced organ support (ADVOS) system allows to eliminate water-soluble as well as protein-bound molecules. Despite its clinical features, to date nothing is known about the elimination of clinically relevant drugs such as antiinfectives. Therefore, we report a case treated with ADVOS, continuous renal replacement therapy (CRRT), and meropenem (1 g 8-hourly) for empiric sepsis therapy monitored by meropenem drug levels. ADVOS showed more efficient elimination of meropenem compared to CRRT which has to be considered when evaluating dosing regimens.